JURISPRUDENTIAL ADAPTATION OF ARTIFICIAL INTELLIGENCE WORKS AND SOME OF THEIR JURISPRUDENTIAL APPLICATIONS - Prof. Dr. Ahmed Shakir Mahmood; Assistant Professor Dr. Hana Muhammed Hussen Ahmed; Assistant Professor Dr. Asmaa Abdul Jabbar Awda; Assistant Professor Dr. Ibrahim Jalil Ali Hussein (Scholars Digest Publishing, 2024)
In the name of God who is praised for His blessings, and prayers and peace be upon the one after whom there is no prophet (Muhammad, may God bless him and grant him peace)... Now then Thinkers and philosophers since ancient times have been trying to know what the elements are, how they work, and the modern nature of human communication and orientation, through which it is possible to predict the behaviors that may affect him.. But what concerns us here is the work of robots that have humans with highly intelligent technologies, and the robot will become famous for its attractive intelligence, and it relies on a phrase: Advanced software...but this intelligence did not exist. Rather, it was artificial intelligence that was predicted in advance by an external will. The problem of the research lies in revealing the nature of artificial intelligence so that we can distinguish it from natural or intrinsic intelligence, and thus arriving at the jurisprudential rulings related to its applied works. Our research sheds light on adaptive conditioning It is for the actions of robots (artificial intelligence) to know their legal ruling in terms of the permissibility or prohibition of behavior in Islamic law. This is of the necessary importance for the life of the Muslim individual, since our religion is the religion of this world and the afterlife, and it works to bring interests and ward off harms to the individual and society.
Keywords: Jurisprudential adaptation - Artificial intelligence – Jurisprudence.